A Systematic Literature Review of Total Productive Maintenance on Industries - Setiawan San (Performa: Media Ilmiah Teknik Industri, 2021)
Attempts to achieve optimization of machine and equipment maintenance at manufacturing companies over the years have encountered a multitude of problems. Due to equipment losses such as setup and adjustment, minor stops and delays, defective products due to equipment, reduced engine speed, and reduced output has influenced their desire to reach world class manufacturing levels. This paper discusses a large part of the TPM approach in manufacturing companies and provides an overview of the various TPM implementation practices demonstrated by manufacturing companies in the world.. Based on review results of the 50 journals about TPM in industries It was found that most of the TPM implementations used the OEE parameter to see the success rate of implementing this TPM. This paper also highlights the variable approach that is most widely used by various practitioners and researchers and evaluates in detail the success factors of implementing TPM and the reasons behind the failure of implementing TPM are also discussed so as to ensure the implementation of TPM can run smoothly and effectively in manufacturing companies